Direct and indirect written corrective feedback in learning writing: The students' perception - Sahmadan, Safrudin; Hasan, Idhar (Univeritas Papua, 2023)
This study was carried out based on the hottest issue regarding the role of direct and indirect written corrective feedback (WCF). The role and use of direct WCF and indirect WCF have been debated issues among second language acquisition and writing researchers. The controversial issue regarding the necessity of feedback started from Truscott’s comment that direct written corrective feedback does not improve students’ writing skills. This research explored the students’ perception of direct WCF and indirect indirect WCF. Qualitative descriptive was applied in this research involving 30 students as the subject. A questionnaire and interview were carried out as the instruments in collecting data. An interactive model that included data collecting, coding, data display, and conclusion or verification was employed for the data analysis. The findings suggested that direct written corrective feedback had a beneficial impact because 99.91% of students said they preferred it.